2005
DOI: 10.1021/ma051582d
|View full text |Cite
|
Sign up to set email alerts
|

Pressure Effect on the Hydration Properties of Poly(N-isopropylacrylamide) in Aqueous Solution Studied by FTIR Spectroscopy

Abstract: The hydration properties of poly(N-isopropylacrylamide) in aqueous solution were investigated by Fourier transform infrared spectroscopy as a function of high hydrostatic pressure and compared to the thermally induced changes. We show that although both pressure and temperature induce a phase separation the underlying mechanisms are fundamentally different. It is well documented that increasing the temperature above the lower critical solution temperature causes a dehydration of the hydrophilic and hydrophobic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
112
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(125 citation statements)
references
References 44 publications
13
112
0
Order By: Relevance
“…In accordance with the Flory theory, the solubility of PS in cyclohexane decreases and its UCST shifts towards lower polymer concentrations on increasing the polymer molar mass. Non-ionic polymers can also undergo a coil-globule transition in aqueous solutions [82][83][84][85][86][87][88][89][90][91][92][93][94][95][96][97][98][99]. However, their transition significantly differs from the transition of polymers in organic media.…”
Section: Sensitivity and Responsivenessmentioning
confidence: 99%
See 1 more Smart Citation
“…In accordance with the Flory theory, the solubility of PS in cyclohexane decreases and its UCST shifts towards lower polymer concentrations on increasing the polymer molar mass. Non-ionic polymers can also undergo a coil-globule transition in aqueous solutions [82][83][84][85][86][87][88][89][90][91][92][93][94][95][96][97][98][99]. However, their transition significantly differs from the transition of polymers in organic media.…”
Section: Sensitivity and Responsivenessmentioning
confidence: 99%
“…This causes intra-and intermolecular aggregation leading to collapse of the individual polymer chains (microphase separation) and precipitation of the polymer (macrophase separation). The LCST depends upon pressure [97,98] and the polydispersity of the polymer. The solution demixing is reversible when the temperature drops below T dem ; however, the rate of polymer redissolution is often slower and the chain expansion takes place at a lower T , which results in a so-called .…”
Section: The Lcst-type Transitionmentioning
confidence: 99%
“…Heating the PNIPAm aqueous solution above LCST leads to the transition of the PNIPAm coils to the collapsed compact globules that aggregate to larger particles but no macroscopic phase separation occurs [8][9][10][11]. It was shown in many studies that the temperature-induced coil-to-globule transition of PNIPAm can be influenced by various parameters such as the tacticity of the polymer [12], pressure [13], the presence of salts [14] or the presence of surfactants [15]. Amphiphilic diblock copolymers in which PNIPAm is the hydrophilic block, such as poly(N-isopropyl acrylamide)-block-polystyrene [16,17] form (PNIPAm-b-PS) micelles with thermoresponsive shells in aqueous solutions.…”
Section: Introductionmentioning
confidence: 99%
“…This result was not anticipated due to the expected precipitation of the catalyst complex above the LCST of 33°C. We found that the LCST of this complex also has a pressure component for which there is literature precedent [29][30][31]. The filtrate of the hot suspension after depressurization exhibits no color and demonstrates no activity for hydrogenation of butenol.…”
Section: High Pressure Flow-through Catalysismentioning
confidence: 87%